A mathematical model structured by age groups and varying the population size to predict the users of e-commerce over the next few years (2018)
The electronic commerce (e-commerce) is an economic activity wich volume has increased over the last few years. The possibility of purchasing the desired product anywhere and anytime, and receive it at home is an attractive service. Also, the price of the goods can be compared in several shops easily. Then, it is expected that e-commerce will keep increasing over the next years. The estimation of this growth could be useful to find out how the shopping may change over the next few years. In this chapter, we propose an age-structured diffusion model with varying population size to study the use of e-commerce as a habit susceptible to be transmitted among peers. Then, using data from the Spanish Statistics Institute (INE) we find the models parameters that make the model to fit the data. With these parameters, we can estimate the users of e-commerce in Spain over the next few years.